Penyelenggaraan Pengobatan Tradisional di Indonesia - Ni Putu Sri Wahyuni (UHN IGB Sugriwa Denpasar, 2021)
The implementation of health services is very important in supporting public health. Treatment with traditional approaches as part of current efforts is often found in Indonesia as part of alternative or complementary health therapies along with conventional health services that can be directed to create a holistic or holistic healthy society. Health is meant to be physically, psychologically, mentally and spiritually healthy. In its application, traditional health has developed into Empirical Traditional Health Services, whose benefits and safety are empirically proven; and Complementary Traditional Health Services, whose benefits and safety are scientifically proven and utilize biomedical science. Based on the method of treatment, Complementary Empirical Traditional Health Services and Traditional Health Services are divided into services that use skills and services that use ingredients or herbs. The traditional approach to treatment is more holistic (whole), while the treatment approach is symptomatic (therapeutic focus is on the symptoms caused). Meanwhile, the implementation process and regulations related to traditional medicine in Indonesia are currently regulated in the Act, the Minister of Health, and the Governor's Regulation.